Marine-Derived Chitosan Biopolymers as Antibacterial Agents: A Review - Nurhadis, Nurhadis; Kasasiah, Ahsanal; Hitopik, Asman (Jurnal Pijar Mipa, 2024)
The growing issue of bacterial resistance to conventional antibiotics has led to an increasing need for alternative antimicrobial agents. Chitosan, a biopolymer derived from marine organisms such as crustaceans (shrimp, crabs) and mollusks (shellfish), has shown significant antibacterial properties. This systematic review aims to evaluate the antibacterial activity of chitosan extracted from various marine sources against Gram-positive (Staphylococcus epidermidis) and Gram-negative (Escherichia coli) bacteria. A comprehensive search of studies published in the past decade was conducted across multiple databases, using predefined inclusion criteria to identify relevant experimental research that focused on quantitative data, such as inhibition zones. The review analyzes key variables, including chitosan extraction methods, concentrations, and experimental conditions. The results revealed that chitosan exhibited the highest antibacterial activity against E. coli, while S. epidermidis showed moderate susceptibility. Variations in antibacterial effectiveness were attributed to differences in chitosan extraction methods and experimental conditions. Despite these variations, the overall evidence supports the potential of chitosan as an effective antimicrobial agent, demonstrating significant inhibition against a wide range of bacterial strains. The findings suggest that chitosan may serve as a promising natural alternative to combat bacterial infections, particularly those caused by antibiotic-resistant pathogens. However, further research is needed to standardize extraction techniques, explore the antibacterial mechanisms, and conduct in vivo studies to validate its clinical applications. These findings underscore chitosan's potential as a sustainable and effective solution in addressing the global challenge of bacterial resistance.